2016
DOI: 10.1089/scd.2015.0298
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Secretome of Human Stem Cells from Dental Apical Papilla

Abstract: Recent studies have shown that secretion of bioactive factors from mesenchymal stem cells (MSCs) plays a primary role in MSC-mediated therapy; especially for bone marrow-derived MSCs (BMSCs). MSCs from dental apical papilla (SCAPs) are involved in root development and may play a critical role in the formation of dentin and pulp. Bioactive factors secreted from SCAPs actively contribute to their environment; however, the SCAPs secretome remains unclear. To address this and gain a deeper understanding of the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…Comparing MSCs from apical papilla-CM to bone marrow MSC-CM, proteins responsible for angiogenesis, immunomodulation, chemotaxis, neuroprotection, antiapoptosis, and extracellular matrix formation were detected in both CM. A significant difference in the levels of 151 of the detected proteins was however noticeable between the two cell sources, where MSCs from apical papilla-CM was associated with higher levels of proteins related to metabolic processes and transcription in addition to chemokines and neurotrophins and lower levels of proteins responsible for adhesion, immunomodulation, angiogenesis, and extracellular matrix proteins [104]. MSCs from the apical papilla-CM, dental follicle MSC-CM, and dental pulp MSC-CM showed a common expression of 174 cytokines.…”
Section: Comparison Between Secretome/conditioned Media Derived From mentioning
confidence: 94%
“…Comparing MSCs from apical papilla-CM to bone marrow MSC-CM, proteins responsible for angiogenesis, immunomodulation, chemotaxis, neuroprotection, antiapoptosis, and extracellular matrix formation were detected in both CM. A significant difference in the levels of 151 of the detected proteins was however noticeable between the two cell sources, where MSCs from apical papilla-CM was associated with higher levels of proteins related to metabolic processes and transcription in addition to chemokines and neurotrophins and lower levels of proteins responsible for adhesion, immunomodulation, angiogenesis, and extracellular matrix proteins [104]. MSCs from the apical papilla-CM, dental follicle MSC-CM, and dental pulp MSC-CM showed a common expression of 174 cytokines.…”
Section: Comparison Between Secretome/conditioned Media Derived From mentioning
confidence: 94%
“…At specific time points (0 h, 24 h, 48 h, 72 h, 96 h), the cultures were supplemented with cell counting kit-8 (CCK-8) solution (Dojindo, Japan) and incubated for 1 h at 37 °C. Cell proliferation was measured at a wavelength of 450 nm by a microplate reader 32 .…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, it has been shown that, under serum, glucose, and oxygen deprivation (SGOD) conditions, SCAP release higher numbers and amounts of proangiogenic factors (Angiogenin, IGFBP-3, and VEGF) and lower amounts of antiangiogenic factors (Serpin-E1, TIMP-1, and TSP-1) in comparison with SOD or SD alone, providing insights into the optimal preconditioning strategies for SC-based treatment of damaged/ischemic tissues [58]. Most recently, SCAP secretome has been extensively profiled [131]; it was found that a total of 2,046 proteins are released, including chemokines, angiogenic, immunomodulatory, antiapoptotic, and neuroprotective factors, and ECM proteins. SCAP secreted significantly larger amounts of chemokines and neurotrophins than BMMSCs, whereas BMMSCs secreted more ECM proteins and proangiogenic factors.…”
Section: Differentiation Potential and Paracrine Activity Of Dentamentioning
confidence: 99%